Implementing sidik gizi: A digital screening program for mapping nutritional status of adolescents in islamic boarding school - Fatati Larasati; Rifqy Rosyidah Ilmi; Alya Nabilah (Institute of Accounting Research and Novation (IARN), 2026)
Traditional, paper-based health logging in residential schools often hinders timely public health responses due to manual diagnostic calculation lags. This study aimed to implement and evaluate